Aggregation and adhesion ability of various probiotic strains and Candida species: An in vitro study - Panita Chantanawilas; Nuntiya Pahumunto; Rawee Teanpaisan (Elsevier, 2024)
Background/purpose: The ability of probiotics to inhibit Candida adhesion is a crucial characteristic that prevents Candida colonization and infection progression. This study aimed to explore aggregation, adhesion, and cell surface characterization of probiotic and Candida strains and to evaluate the effect of probiotics and their cell-free supernatants (CFSs) as postbiotics on Candida adhesion to human oral keratinocytes. Materials and methods: Eight probiotic strains and five reference Candida strains were tested for autoaggregation, coaggregation, adhesin on human oral keratinocytes (H357), and cell surface properties. The anti-Candida adhesion activities of probiotic strains and CFSs were investigated. Results: The results showed that most probiotics exhibited high adhesion to H357 cells, specifically oral probiotic Lacticaseibacillus rhamnosus SD4, Limosilactobacillus fermentum SD7, and L. rhamnosus SD11, and adhesion ability of probiotic strains was strongly related to their autoaggregation, cell surface charges, and hydrophobicity. Candida strains also revealed a high level of adhesion to H357 cells. Candida albicans and Candida glabrata showed significantly higher adhesion abilities than others. After a combination of Candida with probiotics or their CFSs, Candida adhesion was significantly reduced. The anti-Candida adhesion property of probiotics was strongly related to their autoaggregation, coaggregation, and adhesion abilities. Conclusion: This study demonstrated that oral probiotic strains may be useful probiotics for preventing and treating oral candidiasis due to their high ability of aggregation, adhesion, and anti-Candida adhesion to H357 cells.